THE IMPLEMENTATION OF TRANSLINGUAL APPROACH IN WRITING DESCRIPTIVE TEXT - Lia Herlina (Journal of English Education Program (JEEP), 2017)
This article reports on the implementation of translingual approach in writing descriptive text, particularly at the tenth grade of a senior high school in Ciamis. This study aimed at investigating the implementation of translingual approach in teaching writing descriptive text and figuring out the teacher’s reasons of implementing translingual approach. A qualitative approach, particularly case study design, was employed in this study. In this study, the samples were chosen purposively. The selected samples were one class at the tenth grade students and one English teacher. The data of this study were obtained from several sources, including classroom observations and interview with the teacher. The results of this study showed that in teaching writing descriptive text by means of translingual approach, the teacher employed the two basic procedures of the instruction model in implementing translingual approach. With regard to the results, the researcher concludes that the implementation of translingual approach in teaching writing descriptive text has supported the teaching-learning process in the classroom. The impact of this approach stresses more on learning process than the goal of learning, makes the teaching-learning goal could not be achieved optimally in short time because its process takes time consuming.